Performance Analysis Of A Spark Ignition Engine Using Compressed Natural Gas (CNG) As Fuel - Musthafah, Mohd Tahir; M.S., Ali; M.A., Salim; Rosli, A. Bakar; Fudhail, Abdul Munir; Muhammad Zahir, Hassan; Abdul Muhaimin, Mohd Shafie (Elsevier Ltd., 2015)
Compress natural gas (CNG) is also considered as alternative fuel to produce better emission in a vehicle, but the main disadvantage of CNG in comparison to liquid fuel (gasoline) is the lack of power produced for the same capacity of engine. In this study, the single cylinder spark ignition (SI) engine was selected in order to study the effect CNG into the spark ignition engine. The hydraulic dynamometer was used to study the performance of CNG and liquid fuel. The usage of sensor also applies to the test to extract the data during the ignition stage for liquid fuel and CNG. The heat generated by both types of fuel also had been extracted from the tested engine in order to define which usage of fuel would cause a higher heat transfer to the engine. From this study, the result showed that pressure inside cylinder for CNG is 20% less than gasoline. CNG fuel also produced 23% less heat transfer rate compared to gasoline. The results explained why CNG produced 18.5% lower power compared to liquid fuel (gasoline).So, some improvement needs to be done in order to use CNG as fuel.